Copper–Bispidine Complexes: Synthesis and Complex Stability Study - Medved’ko, Aleksei V; Egorova, Bayirta V; Komarova, Alina A; Rakhimov, Rustem D; Krut’ko, Dmitri P; Kalmykov, Stepan N; Vatsadze, Sergey Z (ACS omega, 2016)
A new series of dicarboxylic derivatives of bispidines have been synthesized to develop novel copper(II) complexes suitable as imaging agents for positron emission tomography. For characterization purposes, copper complexes of bispidines were synthesized in the pure form and in quantitative yields by neutralization of ligands with malachite. The formation of complexes and their stoichiometries were studied by potentiometric titration, cyclic voltammetry, and spectroscopic methods. The stability constants were found to be fairly suitable for copper cation fixation inside dianionic chelate molecules.